Becoming Barnabas: The Ministry of Encouragement - Moots, Paul, (Rowman & Littlefield Publishers, 2004)
Western culture has made a cult of success, and the church has accepted the larger culture's definition, focusing on success as growth in membership and budget, rather growth in faithfulness as disciples of Jesus. When we do not measure up, we become discouraged, disillusioned, and perhaps even envious. Moots details numerous examples to show how the ministry of encouragement offers a workable, effective pattern for church leadership. "I am convinced," he writes, "that accepting Barnabas as my model has changed my ministry for the better and that Barnabas's example can benefit any pastor and congregation who take his lessons seriously. Barnabas and his ministry of encouragement offer us a focus for the vital, messy, and exhilarating work required of us as faith communities.